An Anthropology of Absence Materializations of Transcendence and Loss - Bille, Mikkel; Hastrup, Frida; Soerensen, Tim Flohr; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
In studying material culture, anthropologists and archaeologists use meaningful physical objects from a culture to help understand the less tangible aspects of that culture, such as societal structure, rituals, and values. What happens when these objects are destroyed, by war, natural disaster, or other historical events? Through detailed explanations of eleven international case studies, the contributions reveal that the absence of objects can be just as telling as their presence, while the objects created to memorialize a loss also have important cultural implications. Covering everything from organ donation, to funerary rituals, to prisoners of war, The Anthropology of Absence is written at an important intersection of archaeological and anthropological study. Divided into three sections, this volume uses the "presence" of absence to compare cultural perceptions of: material qualities and created memory, the mind/body connection, temporality, and death. This rich text provides a strong theoretical framework for anthropologists and archaeologists studying material culture.
Toward an Anthropology of Absence -- Introduction: An Anthropology of Absence -- People Without Things -- Embodying Absence -- Missing Bodies Near-at-Hand: The Dissonant Memory and Dormant Graves of the Spanish Civil War -- A Sense of Absence: The Staging of Heroic Deaths and Ongoing Lives among American Organ Donor Families -- Temporalities of Absence -- Derivative Presence: Loss and Lives in Limbo in the West Bank -- Materializations of Disaster: Recovering Lost Plots in a Tsunami-Affected Village in South India -- Materializing Remembrance -- A Saturated Void: Anticipating and Preparing Presence in Contemporary Danish Cemetery Culture -- Bringing Home the Dead: Photographs, Family Imaginaries and Moral Remains -- Ambiguous Materialities -- Absent Powers: Magic and Loss in Post-socialist Mongolia -- Seeking Providence Through Things: The Word of God Versus Black Cumin -- Presencing the Im-Material -- Commentary -- An Anthropology of Absence: Commentary.
Keywords: Social sciences; Cultural heritage; Anthropology; Social Sciences; Anthropology; Cultural Heritage; Electronic books